2013
DOI: 10.3386/w19649
|View full text |Cite
|
Sign up to set email alerts
|

Dishonesty and Selection into Public Service

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 30 publications
4
52
2
Order By: Relevance
“…This contrasts with other recent studies of dishonesty in the lab and in the field which target much more specific populations (open air sellers in List, 2009; bankers in Cohn et al, 2014; prisoners in Cohn et al, 2015;graders in Armantier and Boly, 2013; nurses in Hanna and Wang, 2015). Regarding the risk of self-selection, comparisons with data collected by the !…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This contrasts with other recent studies of dishonesty in the lab and in the field which target much more specific populations (open air sellers in List, 2009; bankers in Cohn et al, 2014; prisoners in Cohn et al, 2015;graders in Armantier and Boly, 2013; nurses in Hanna and Wang, 2015). Regarding the risk of self-selection, comparisons with data collected by the !…”
Section: Introductionmentioning
confidence: 80%
“…The experiment most closely related to our study is that of Hanna and Wang (2015), run in India. It shows that nurses who report more favorable outcomes in a die rolling task are more likely to be absent from work.…”
mentioning
confidence: 99%
“…A study in India measures the propensity to cheat among 669 final-year college students in the city of Bangalore using a dice game [12]. It also measures pro-sociality using a dictator game, similar to the one described above for the Zambia study [11].…”
Section: What Can Be Done To Improve Recruitment In the Public Sector?mentioning
confidence: 99%
“…Another recent working paper by Hanna and Wang (2014) studies cheating in a sample of government nurses in India. They found that nurses who cheated more in a dice task also tended to show up at work less often.…”
Section: Introductionmentioning
confidence: 99%